Xiao-Yao-San, a Chinese Medicine Formula, Ameliorates Chronic Unpredictable Mild Stress Induced Polycystic Ovary in Rat - Sun, Hao-Yu; Li, Quan; Liu, Yu-Ying; Wei, Xiao-Hong; Pan, Chun-Shui; Fan, Jing-Yu; Han, Jing-Yan (Frontiers in Physiology, 2017)
Chronic stress induces endocrine disturbance, which contributes to the development of polycystic ovary syndrome (PCOS), a condition that remains a challenge for clinicians to cope with. The present study investigated the effect of Xiao-Yao-San (XYS), a traditional Chinese medicine formula used for treatment of gynecological disease, on the chronic stress-induced polycystic ovary and its underlying mechanism. Female Sprague-Dwaley rats underwent a 3 weeks chronic unpredictable mild stress (CUMS) procedure to establish the PCOS model, followed by 4 weeks treatment with XYS (0.505 g/kg or 1.01 g/kg) by gavage. Granulosa cells were exposed to noradrenaline (1 mM) in vitro for 24 hours, followed by incubation with or without XYS-treated rat serum for 24 hours. Post-treatment with XYS ameliorated CUMS-induced irregular estrous cycles and follicles development abnormalities, decrease of estradiol and progesterone level as well as increase of luteinizing hormone in serum reduced cystic follicles formation and the apoptosis and autophagy of granulosa cells, attenuated the increase in dopamine beta hydroxylase and c-fos level in locus coeruleus, the noradrenaline level in serum and ovarian tissue, and the expression of beta 2 adrenergic receptor in ovarian tissue. Besides, XYS alleviated the reduction of phosphorylation of ribosomal protein S6 kinase polypeptide I and protein kinase B, as well as the increase of microtubule-associated protein light chain 3-I to microtubule-associated protein light chain 3-II conversion both in vivo and in vitro. This study demonstrated XYS as a potential strategy for CUMS induced polycystic ovary, and suggested that the beneficial role of XYS was correlated with the regulation of the sympathetic nerve activity.